2018
DOI: 10.1016/j.gie.2018.04.1988
|View full text |Cite
|
Sign up to set email alerts
|

Mo1338 COMPARISON OF EUS DIRECTED TRANSGASTRIC ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY (EDGE) WITH LAPAROSCOPIC GUIDED ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY IN PATIENTS WITH ROUX-EN-Y BYPASS: A META-ANALYSIS

Abstract: specimen was more commonly obtained with EUS-TTNB (88.2%) compared to EUS-FNA (51.9%) (p<0.001). For cysts with insufficient amount of fluid for CEA (nZ19) or CEA<192 ng/mL (nZ22), the cumulative incremental diagnostic yield of a mucinous cyst was significantly higher with EUS-TTNB (51.2%) compared to EUS-FNA (17%) (pZ0.002). Nine (17%) patients underwent surgical resection. Surgical pathology was positive for a mucinous cyst (intrapapillary mucinous neoplasm or mucinous cystic neoplasm) in 7 cases, of which E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In 2018, a meta-analysis comparing LA-ERCP and EDGE including 941 patients (843 LA-ERCP and 98 EDGE) showed pooled technical and clinical success rates similar in both of the groups (98% vs. 96%, p = 0.07 and 96% vs. 96%, p = 0.84). AE rate had no significant difference (13% vs. 10%, p = 0.32) [ 71 ]. Data reported by Khara et al confirmed a high success rate among 76 patients in both those who performed LA-ERCP and EDGE (both 100%), with no significant difference in adverse events rate (17%vs.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, a meta-analysis comparing LA-ERCP and EDGE including 941 patients (843 LA-ERCP and 98 EDGE) showed pooled technical and clinical success rates similar in both of the groups (98% vs. 96%, p = 0.07 and 96% vs. 96%, p = 0.84). AE rate had no significant difference (13% vs. 10%, p = 0.32) [ 71 ]. Data reported by Khara et al confirmed a high success rate among 76 patients in both those who performed LA-ERCP and EDGE (both 100%), with no significant difference in adverse events rate (17%vs.…”
Section: Resultsmentioning
confidence: 99%
“…All EDGE-related studies have demonstrated higher technical (100%) and clinical success rates (60%–100%) [ 41 – 47 , 54 ]. EDGE has similar success rates (96.5% vs 100% p = 0.40) as compared to LA-ERCP in achieving therapeutic ERCP, but appears superior when compared to DAE (100% vs 60%, p < 0.001) [ 48 – 50 ]. Although LA-ERCP and EDGE have similar success rates, EDGE has shorter procedure time (73 vs 184 min, p < 0.00001) and post procedural hospital stay (0.8 vs 2.65 d, p < 0.00008) [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Technical and clinical success rates were similar in both the groups (98% vs 96% p = 0.07 and 96% vs 96% p = 0.84) without any significant difference in the adverse event rate (13% vs 10%, p = 0.32). However, pooled mean length of stay and procedure time were shorter with EDGE (1.1 vs 3.1 days and 43 min vs 166 min) [ 50 ].…”
Section: Advanced Endoscopy Techniquesmentioning
confidence: 99%